Purpose-driven innovation : lessons from managing change in the United Nations - Flanding, Jens P.; Grabman, Genevieve Marie, 1975- (Emerald Publishing, 2022)
Purpose-Driven Innovationis the first book to set out how change management models work in practice in the context of the Sustainable Development Goals (SDGs), an essential primer for all organizations, small and large, public or private, within and outside of the United Nations in the wake of crisis.